MOLECULAR DYNAMICS SIMULATION OF DIMERIC HUMAN BETA DEFENSIN 3 PROTEIN - ARTIKA WIZARINI ( NIM : 10507012 ); Pembimbing : Dr. Santi Nurbaiti,
Human Beta Defensin 3 (HBD3) is an antimicrobial peptide that thought to form dimer in native conformation. In this research, we have performed dimerization of HBD3 monomer and molecular dynamics simulation of HBD3 dimer in water. The objective of this research is to design the dimeric structure of HBD3 approaching its native conformation and determine the stability of HBD3 dimer obtained. Dimerization of HBD3 monomer (PDB code: 1KJ6, first model) has been carried out using SymmDock. Analyses of the orientation of dimer conformation, the length of hydrogen bond at the interface of Beta2-sheet, and dimmers potential energy obtained by a candidate named HBD3WT (Gln29(Beta2,I)-Gln29(beta2,II): 12,34 A). In order to find the best dimer conformation, the distances between HBD3WT monomers was modified obtained the HBD3HN and HBD3N (Gln29(Beta2,I)-Gln29(Beta2,II): 6,6 and 2,53 A). Molecular dynamics simulation on the three structures performed at 300 and 310 K. Analyses of the Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF), secondary structure stability, Solvent Accessible Surface Area (SASA), residues interaction that stabilize the monomer (Ile30-Tyr10, Arg17-Cys41, Ala19-Lys39, Arg42-Glu28, and Cys40-Ile30) and the dimer (Gln29(Beta2,I)-Gln29(Beta2,II)) obtained HBD3N structure as the best HBD3 dimer structure.